A Cost Variation Analysis of Oral Contraceptive Pills available in the Indian market - Chethan B (Journal of Pharmacoeconomics and Pharmaceutical Management, 2023)
Background: Oral Contraceptive Pills (OCPs) are highly effective contraceptives if used regularly and adequately, and they also have added non-contraceptive benefits. This gives way to their increasing use in recent years, which has led to the introduction of numerous brands of drugs with different costs in the Indian market. Hence the current study was conducted to analyze the cost ratio and cost variation of different brands of OCPs available in the Indian market and to compare the cost of branded and generic drugs.